PERGESERAN PENGGUNAAN TENUN IKAT PADA MASYARAKAT DESA TANAH PUTIH (Verba Vitae Unwira, 2020)
THE SHIFT OF HABIT OF WEARING WOVEN CLOTH OF THE TANAH PUTIH VILLAGE COMMUNITIESWoven fabric in Tanah Putih village is unique because its motives are different from those of neighboring village's. Therefore, this woven fabric is a marker of local community identity when interacting with outside communities. This weaving also shows the social stratification of the local community. However, nowadays, the woven fabric almost becomes extinct because the number of weavershas decreased. The patternsused to marksocial stratification have also disappeared. Bythis case study with its descriptive data, this article tries to trace the journey of the woven cloth of the Tanah Putih Village community -its types, motives and meanings and the factors that causethe shift.
Keywords: Woven Fabrics; Culture; Communication; Motives; Meanings